Synthesis of Automatic Control System of Step-Up DC Voltage Converter Operating in Boundary-Continuous Current Conduction Mode - A. V. Mironovich; P. P. Primshits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper investigates an operation of a step-up DC voltage converter in the mode of boundary-continuous restrictor current. Functional diagram of a logic unit ensuring boundary-continuous mode has been developed. A mathematical model of a converter operating in a boundary-continuous mode, has been built in the paper. Comparative transient simulation in a linear structure and a model on the basis of power element library have been carried out with the help of a computer.